Cornerstones for the Cross-border Attorney Service and the Importance of the EU-En4s Project and Partner Networking - Bores Lazo Jesús (LeXonomica, 2022)
Many papers and contributions identify the processes by which consistent cross‐border service to the client may be achieved within globally integrated firms. The role of international attorneys is becoming very complex due to new global challenges. To surpass these obstacles, the principal solution is to cooperate and develop close collaboration with colleagues. This is why projects such as EU-En4s Diversity of Enforcement Titles in cross-border Debt Collection in EU, led by the University of Maribor, are so relevant. Povzetek. Številni članki in prispevki opredeljujejo postopke, s katerimi je mogoče v globalno povezanih podjetjih doseči dosledno čezmejno storitev za stranko. Vloga mednarodnih odvetnikov postaja zaradi novih globalnih izzivov zelo zapletena. Za premagovanje teh ovir je glavna rešitev sodelovanje in razvijanje tesnega sodelovanja s kolegi. Zato so projekti, kot je EU-En4s Diversity of Enforcement Titles in cross-border Debt Collection in EU, ki ga vodi Univerza v Mariboru, tako pomembni.